A study on factors influencing stress among workers at Malaysia Airports Holding Berhad / Ibrahim Zazali - Zazali, Ibrahim (2011)
Now-a-days everyone talks about stress. It is cutting across all socio-economic groups of population and becoming the great leveler. Not only just high-pressure executives are its key victims but it also includes laborer’s, slum dwellers, working women, businessmen, professionals and even children. Stress is an inevitable and unavoidable component of life due to increasing complexities and competitiveness in living standards. The speed at which change is takin place in the world today is certainly overwhelming and breathe taking. In the fast-changing world of today, no individual is free from stress and no profession is stress free. This research will determine which of the factor between demographic factor, organizational factor and interpersonal relationship have the most influence factor on stress. A Likert-type scale has been developed and tested in this study. The result of this research were obtained by using methods analysis such as reliability test, frequency distribution, and pearson correlation. Pearson correlation was using to identify the relationship between the independent variable and dependent variable. The process of analyzing and interpreting of data was presented through tables.